Al-Qur'an dan Upaya Pemanusiaan Penuh Perempuan - Nor Khalim (Mathematics Education Study Program, 2025)
This article analyzes the effort of full humanization of women through the perspective of the Qur'an. The fundamental issue is the existence of patriarchal-biased interpretations of religious texts, which often legitimize the subordination of women, even though Islam essentially comes with the mission to elevate their status. The purpose of this study is to trace the basic principles of gender equality in the Qur'an and to examine the reconstructive efforts of understanding carried out by contemporary Muslim thinkers. The method used is a qualitative literature study by deeply analyzing primary literature (the Qur'an) and secondary sources (tafsir, books, and academic journals). The results show that the Qur'an lays the foundation of equality through the principle of creation from nafsin wāhidah (one soul), equality as servants and caliphs, as well as equality in deeds and rewards. Moreover, a hermeneutic rereading of gender-sensitive verses—such as leadership, inheritance, and polygamy—reveals a more contextual and just meaning. In conclusion, the full humanization of women is not a foreign agenda but rather an effort to return to the spirit of justice and egalitarianism inherent in the Qur'an, which has long been obscured by culturally biased interpretations.